SOFT-PRIMORDIALISM; GAGASAN MANAJEMEN RELASI AGAMA DAN ETNISITAS ATAS PENGALAMAN MASYARAKAT MUSLIM KUPANG - Dewi, Subkhani Kusuma (UIN Sunan Kalijaga Yogyakarta, 2012)
As migrant citizen, Muslim communities in Kupang mostly live in strong ethnic group. This continues to produce their specific identity in ethnic group, religion, and economical status to separate from the resident. Reading this as a condition of Ashabiyah, this article discusses a superstructure for whole aspect of life which succeeded to grasp power and economic interest. The condition of ethnic identity boundar y was maintained through both exter nal ascription and inter- nal self-identification which continued to result a ‘hard’ primordialism. Hence, ethnic conflict and violence could be a hard risk for the relationship among ethnic groups in Kupang.This article stimulates a more contemporar y fact where ethnic identity goes far beyond biological nature, where the existence of ethnic fusion takes place and plays a potential factor for a ‘soft’ kind of primordialism. It is an agency stage where a member of an ethnic group got two phases; first while one chooses to re-pursue or to re-embrace an ethnic identity, then the second stage one will use an inter-subjective form of self-maintaining identity.